Intellectual capital disclosure of biotechnology companies listed in Asia Pacific - Goh, Riquel Minsi (2008)
This paper uses content analysis to examine annual reports (2004) of 100 listed biotechnology firms in Asia Pacific to investigate factors that influence intellectual capital (IC) disclosure behaviors and to determine the content of IC disclosure.